A Dollar Estimate of Soviet Foreign Trade, 1947-1951 - Herman, L. M. (The Review of Economics and Statistics, 1954)
THE pattern of Soviet participation in foreign trade since World War II has been radically altered as a result of the farreaching changes wrought by the war in the international relations of the U.S.S.R. Unfortunately, firm and direct information on Russia's annual transactions in international trade is unavailable inasmuch as the Soviet Government has continued to maintain a blackout of information, introduced at the end of I938, on this vital subject. Hence the magnitude and geographic direction of Soviet foreign trade can only be determined approximately and indirectly by the use of the statistical returns of the countries trading with the U.S.S.R. A composite estimate of the dollar value of Soviet foreign trade for the five-year period I947 to I95I discloses that the effort which the U.S.S.R. has exerted in recent years to mobilize and direct the resources of the areas in Europe and Asia that have come under its control has resulted in two conspicuous changes in the character of Russia's international exchange of commodities. One distinctive feature of postwar Soviet foreign trade has been a strong upward trend in its total annual value. In this respect, Soviet trade has witnessed a reversal of the trend it displayed during the prewar period, I930 to 1938, when the annual value of Russia's foreign trade had tended downward steadily.